2018
DOI: 10.1186/s12905-018-0652-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of emergency contraception among women with experience of domestic violence and abuse: a systematic review

Abstract: BackgroundExposure to domestic violence and abuse (DVA) results in a reduction of women’s use of regular contraceptives. This evidence suggests that women exposed to DVA are more likely to have unprotected sexual intercourse and therefore may use more emergency contraception (EC) than those women who are not exposed to DVA. We aimed to test this hypothesis through evaluating the evidence for an association between exposure to DVA and use of EC.MethodsWe systematically searched eight electronic databases from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
7
1
Order By: Relevance
“…This study supports the recent systematic review of cross-sectional studies that found some evidence for an association between exposure to DVA and increased use of EC 5. The two main reasons for seeking EC are women’s fear that the contraceptive method they used would not work, and women’s fear of unintended pregnancy after unprotected intercourse 38.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study supports the recent systematic review of cross-sectional studies that found some evidence for an association between exposure to DVA and increased use of EC 5. The two main reasons for seeking EC are women’s fear that the contraceptive method they used would not work, and women’s fear of unintended pregnancy after unprotected intercourse 38.…”
Section: Discussionsupporting
confidence: 88%
“…Two systematic reviews have found an association between exposure to DVA and reduction in use of regular contraception 3 , 4. The authors’ recent systematic review found some evidence for a positive association between exposure to DVA and use of emergency contraception (EC) 5. However, none of these reviews included UK studies.…”
Section: Introductionmentioning
confidence: 99%
“…The study results is consistent with a study done in Egypt assessed the effects of married women's autonomy on utilization of modern FP methods revealed that, married women who are under the control of male partners are also limited to access modern FP (39). These ndings are contrasted with a study done in England and South Asia, which reported that, there is no relationship between married women experienced IPV and modern FP use (40,41). The similar ndings of no association between IPV and modern FP use were also reported from a study done in Uganda (Kidman & Bertrand, 2015; Wandera, et al, 2018).…”
Section: Discussioncontrasting
confidence: 43%
“…When agencies miss an opportunity to intervene effectively, women are at risk of returning to the exploitation and abuse from which they are attempting to escape (Hodges and Burch, 2019;Matthews et al, 2014;WAFE, 2017). Women seeking support to escape abuse do not typically approach specialist services directly (AVA & Agenda, 2019;Lewis et al, 2018). It is therefore crucial that everyone with whom they come into contact, including non-specialist staff in general practice surgeries and other agencies, know how to respond appropriately, which agencies in their locality (women's centers, hostels, refuges, etc.)…”
Section: Discussion Of Findings In the Context Of Existing Studiesmentioning
confidence: 99%